Supramolecular Organogelation Directed by Weak Noncovalent Interactions in Palmitoylated 1, 5‐Anhydro‐d‐Glucitol Derivatives. Issue 4 (8th April 2020) - Kajiki, Takahito; Komba, Shiro; Iwaura, Rika
Abstract: We synthesized a series of novel alicyclic compounds by modifying 1, 5‐anhydro‐d ‐glucitol with two to four palmitoyl chains, and we explored their self‐assembly and gelation behaviors in paraffin. The obtained organogels were studied by field emission scanning electron microscopy, atomic force microscopy, variable‐temperature Fourier transform IR spectroscopy, X‐ray diffraction analysis, polarized optical microscopy, and transmission spectroscopy. While all the palmitoylated derivatives spontaneously formed fibrous networks and gelated the paraffin, an acetylated derivative of 1, 5‐anhydro‐d ‐glucitol did not gelatinize the solvent, thus indicating the importance of aliphatic chains for gelation. Interestingly, α‐ and β‐ d ‐glucopyranose with five palmitoyl chains neither gelatinized the solvent nor formed fibrous networks, thus suggesting that the absence of C‐1 substitution in 1, 5‐anhydro‐d ‐glucitol is important for gelation. Fourier transform IR spectroscopy suggested that the formation of weak hydrogen bonds between the carbonyl groups and the C−H groups was the driving force for formation of the supramolecular fibers and for gelation of the solvent. Abstract : Gelling together : Palmitoylated 1, 5‐anhydro‐d ‐glucitol derivatives form supramolecular fibers and gelatinize organic solvent directed by van der Waals interaction between palmitoyl chains, and weak hydrogen bonds between the carbonyl groups and the C−H groups. In addition, the lack of C‐1 substitution in 1, 5‐anhydro‐d ‐glucitol derivatives are crucial for the formation of one‐dimensional fibers and resulting gelation of the solvent.